2021
DOI: 10.20527/jht.v9i1.10491
|View full text |Cite
|
Sign up to set email alerts
|

Respon Pertumbuhan Anakan Belangeran Terhadap Penyiraman Air Rawa Gambut, Air Tandan Kosong Kelapa Sawit, Dan Kapur Dolomit

Abstract: The research aimed to analyze the growth response of belangeran (Shorea balangeran) seedlings on the water of palm oil empty bunches and dolomite lime. The research used a method of a completely randomized design, with the treatments: dolomite lime water, oil palm empty bunch water, and peat swamp water as a control. Based on the ANOVA, the treatment had a very significant effect on the increase of height and diameter of the seedlings. The dolomite lime water increased the seedling height of 9.434 cm, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Fertilization treatments have been reported to increase the growth of forest tree seedlings and have been widely practiced operationally, in both container-grown and bare-root nurseries [23]. Previous studies have reported the positive effect of NPK fertilization on the growth of forest tree seedlings, such as Mimusops elengi [7], Anthocephalus macrophyllus [8], and Combretocarpus rotundatus [9]. NPK fertilizers consist of three components that supply nitrogen, phosphorus, and potassium.…”
Section: Seedling Performance At the Nurserymentioning
confidence: 99%
See 1 more Smart Citation
“…Fertilization treatments have been reported to increase the growth of forest tree seedlings and have been widely practiced operationally, in both container-grown and bare-root nurseries [23]. Previous studies have reported the positive effect of NPK fertilization on the growth of forest tree seedlings, such as Mimusops elengi [7], Anthocephalus macrophyllus [8], and Combretocarpus rotundatus [9]. NPK fertilizers consist of three components that supply nitrogen, phosphorus, and potassium.…”
Section: Seedling Performance At the Nurserymentioning
confidence: 99%
“…The nursery fertilization of tree seedlings has been demonstrated in numerous studies. The studies demonstrated that the availability of nutrients, particularly N, P, and K, is an important factor in tree seedling growth [7][8][9] and the production of healthy seedlings. For a plantation to thrive under stress, healthy seedlings are essential.…”
Section: Introductionmentioning
confidence: 99%
“…Knowing the optimum height growth of the mersawa seedlings will make it easier to find locations for planting the seedlings in peat swamp land based on inundation height. Furthermore, according to Achmad and Bakri (2021), the pH of the peat swamp water is very acidic (pH 3.5), and therefore, it needs to increase.…”
Section: Introductionmentioning
confidence: 99%
“…To increase pH of peat swamp water, Achmad and Bakri (2021) have proven that adding oil palm empty fruit bunches (OPEFB) and dolomite lime was able to increase the pH of the peat swamp water and increase the growth of belangeran (Shorea balangeran) seedlings by watering peat swamp water mixed with OPEFB, and dolomite on the seedlings. In addition, Achmad and Bakri (2022) found that the growth of Kalimantan swamp jelutung (Dyera polyphylla) seedlings were susceptible to inundation height.…”
Section: Introductionmentioning
confidence: 99%